IMF Research Bulletin, September 2006 - Spilimbergo, Antonio (IMF Research Bulletin; IMF Research Bulletin ;, 2006)
Research summaries on (1) measuring inflation, and (2) strengthening Poverty Reduction and Growth Facility (PRGF) programs through poverty and social impact analysis (PSIA); country study on Spain; listing of contents of Vol. 53, Special Issue of IMF Staff Papers, summary of recently published IMF book entitled "IMF-Supported Programs: Recent Staff Research"; listings of recent external publications by IMF staff members, IMF Working Papers, and visiting scholars at the IMF during January-August 2006.